The Impact of a Multifaceted Pharmacist-Led Antimicrobial Stewardship Program on Antibiotic Use: Evidence From a Quasi-Experimental Study in the Department of Vascular and Interventional Radiology in a Chinese Tertiary Hospital - Xu, Jinhui; Huang, Jian; Yu, YanXia; Zhou, Dayong; Wang, Ying; Xue, Sudong; Shang, Erning; Sun, Jiantong; Ding, Xinyuan; Shi, Lu; Duan, Lufen; Tang, Lian; et al. (Frontiers in Pharmacology, 2022)
Objectives: To assess the impact of multifaceted clinical pharmacist-led antimicrobial stewardship (AMS) program on rational use of antibiotics for the patients who receive vascular and interventional radiology therapies. Methods: A quasi-experimental retrospective intervention design, with a comparison group was applied to the practices of antibiotic use in the department of vascular and interventional radiology in a Chinese tertiary hospital. We used difference-in-differences (DID) analysis to compare outcomes before and after the AMS intervention between intervention group and control group, to determine whether intervention would lead to changes in irrationality of antibiotic prescribing, antibiotic utilization, cost of antibiotics, the length of hospital stay. Results: The DID results showed that the intervention group was associated with a reduction in the average consumption of antibiotics (P=0.017) and cost of antibiotics (P=0.006) and cost per defined daily dose (DDD) (P=0.000). There were no significant differences in mean change of total costs and length of stay between the two groups (P>0.05). The average inappropriate score of perioperative antimicrobial prophylaxis in the intervention group declined by 0.23, while decreased by 0.02 in the control group (0.21 [95% CI, -0.271 to -0.143]; P=0.000). Average inappropriate score of non-surgical antimicrobial prophylaxis in the intervention group declined by 0.14, while increased by 0.02 in the control group (0.16 [95% CI, -0.288 to -0.035]; P =0.010). Average inappropriate score of the therapeutic use of antibiotics in intervention group declined by 0.07, while decreased by 0.01 in the control group (0.06 [95% CI, -0.115 to -0.022]; P=0.003). Conclusions: This study provides evidence that implementation of AMS interventions was associated with a marked reduction of antibiotic use, cost of antibiotics and irrationality of antibiotic prescribing in China.